Pemanfaatan Teknologi Informasi di Pesantren - Abdul Muin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2011)
AbstractThis research aims at finding a response of the islamic boarding school against Information Technology (IT), strategy applied and teacherâ€™s ability in applying it. The research outcome explains that the response of the Islamic boarding school against the IT constitutes a part of ots responses toward modernization. The respon of the Islamic boarding school against the IT that constitutes an adaptive and anticipative act. The adaptive attitude against the IT utilization constitutes as a complement in the learning process. Meanwhile, anticipative attitude is built on an importance of updating the integrated learning process by applying the IT to all activities, particularly in the learning process. A utilization strategy of the IT carried out by the Islamic boarding house could not have evoked any motivation and creativity of the student in the learning process. However, generally the teacher or preacher at the Islamic boarding school coming from different educational background could have maximally applied the information technology.Â AbstrakPenelitian ini bertujuan untuk mengetahui respon pondok pesantren terhadap teknologi informasi (TI), strategi yang digunakan dan kemampuan pendidik menggunakannya. Hasil penelitian menjelaskan bahwa respon pondok pesantren terhadap TI merupakan bagian dari responnya terhadap modernisasi. Respon pondok pesantren terhdap TI merupakan tindakan adaptif dan antisipatif. Sikap adaptif terhadap pemanfaatan TI sebagai pelengkap dalam proses pembelajaran. Sedangkan sikap antisipatif dibangun atas dasar pentingnya pembaharuan proses pembelajaran yang integratif dengan menerapkan TI pada seluruh kegiatan, khususnya dalam proses pembelajaran. Strategi pemanfaatan TI oleh pondok pesantren belum dapat membangkitkan motivasi dan kreatifitas santri salam proses pembelajaran. Namun demikian, umumnya guru atau ustadz di pondok pesantren dari latar belakang pendidikan yang berbeda, telah dapat menerapkan teknologi informasi secara maksimal.Â